海水溶解无机碳原位测定仪的研制 - 戴燕中 (2015)
海水溶解无机碳(DissolvedInorganicCarbon，DIC)是表征海水碳酸盐体系的四大参数之一，也是海洋碳循环和海洋酸化研究的基础数据。目前，海水DIC数据的获取主要依靠科考船采集离散的样品进行分析，由此得到的数据时空分辨率低，无法满足当前海洋科学研究的需求。采用原位仪器进行长时间系列观测是获取高时间分辨率海水DIC数据的最佳手段。目前仍鲜有DIC原位测定仪的报道。本论文研制了原位DIC测定仪(InSituAnalyzerofDissolvedInorganicCarbon，ISA-DIC)，并在实验室、室外水池和海上对其进行性能测试。主要研究内容和结果如下： (1) 以分光光. Dissolved inorganic carbon (DIC) is one of the four parameters characterizing the oceanic CO2 system, and also the basic data for the research of ocean carbon cycle and ocean acidification. So far, most of the DIC data is obtained mainly by analyzing bottle samples collected in cruise. This data is of low spatial and temporal resolution and can not meet the requirement of the research community. T. 学位：理学硕士 院系专业：海洋与环境学院_环境科学 学号：22620101151382